Debt overhang, global growth opportunities, and investment - Barbiero, Francesca; Popov, Alexander; Wolski, Marcin (Journal of Banking & Finance, 2020)
Using a pan-European data set of 8.5 million firms, we find that firms with high debt financing invest relatively more, than otherwise similar firms, if they are operating in sectors facing good global growth opportunities. The positive impact of a marginal increase in debt on investment in good-global-growth-opportunities sectors disappears if firm debt is already excessive, if it is dominated by short maturities, and during systemic banking crises. Our results are consistent with theories of the disciplining role of debt, as well as with models highlighting the negative link between firm- and bank-related agency problems and corporate investment.